Target-strength studies on Atlantic cod (Gadus morhua) in Newfoundland waters - Rose, G. A.; Porter, D. R. (ICES Journal of Marine Science, 1996)
Acoustic target strengths (TS) of Atlantic cod ( Gadus morhua L.) of lengths 12–65 cm were measured ex situ at 38 and 120 kHz (dual beam) under continuous video monitoring. Each fish swam within an acoustically inert monofilament mesh bag secured 10 m beneath fixed location transducers. Overall ex situ target strength–length (L, cm) relationships were TS=20 log L (cm)–66 at 38 kHz and TS=20 log L (cm)–65 at 120 kHz (n=16). Cod TS peaked at aspects of 5–10° off horizontal (head-down). Full rotation directivities spanned 20 dB. Stationary variations of low amplitude (<3 dB) correlated with swimming movements. A linear model was used to study in situ TS (38 kHz) from 49 acoustic-trawl experiments targeted at cod and associated species at depths from 200–375 m. Significant factors were species composition (40% of variance), depth distribution (20%), and time of day (5%; total r2=0.65). Modelled TS (standardized to cod) was 1.5 dB higher at night when cod were up to 140 m off bottom. Night-time TS did not differ from the ex situ TS–daytime TS was significantly lower by 1.5 dB. Our findings are consistent with cod being neutrally buoyant off bottom (night) and negatively buoyant nearer bottom in the day-time. Pooled neutrally buoyant in situ and ex situ TS (38 kHz) indicated the relationship (TS=20 log L–66, r2=0.80, n=39).